Pola Kemitraan Pemerintah Kota Surabaya dan Masyarakat Dalam Pengelolaan Sampah di Jambangan Kota Surabaya - Lisa, Fasihul; Rahmadini, Chesa Fabita; Musleh, Moh; Tamrin, M Husni (Department of Public Administration, Muhammadiyah University of Makassar, 2024)
This research aims to examine the partnership pattern between the Surabaya City Government and the community in waste management in Jambangan. This research uses descriptive qualitative methods by collecting data through observation, interviews and documentation. In this research, several informants from the Jambangan Recycling Center (PDU) Coordinator and informants from the Environmental Service were used. The analysis of the partnership research between the Surabaya City Government and the community in waste management in Jambangan uses Nana Rukmana's Partnership theory (2006) with 3 principles, namely: (1) equality; (2) organizational openness; and (3) principle of mutual benefit. The research results show that the Jambangan PDU as a waste management facility has an important role in reducing waste generation at the Benowo Final Disposal Site (TPA). In the waste management process, waste sorting and processing is carried out in collaboration between PDU officers, community organizers and various related stakeholders. The results of this process have succeeded in reducing waste deposits to landfill by 50% to 60% every month, saving waste transportation costs, and extending the life of the landfill. Waste management at PDU Jambangan involves maggot larvae and a Rooftop Solar Power Plant (PLTSA) to make the process more sustainable and efficient. This partnership pattern provides mutual benefits in efforts to overcome waste problems and protect the environment.